Mechanism of Lipid Accumulation through PAR2 Signaling in Diabetic Male Mice - Kim, Dae Hyun; Kim, Ye Ra; Bang, EunJin; Ha, Sugyeong; Noh, Sang Gyun; Kim, Byeong Moo; Jeong, Seong Ho; Jung, Hee Jin; Lee, Ji Young; Chung, Hae Young (Endocrinology and metabolism (Seoul), 2021)
Protease-activated protein-2 (PAR2) has been reported to regulate hepatic insulin resistance condition in type 2 diabetes mice. However, the mechanism of lipid metabolism through PAR2 in obesity mice have not yet been examined. In liver, Forkhead box O1 (FoxO1) activity induces peroxisome proliferator-activated receptor γ (PPARγ), leading to accumulation of lipids and hyperlipidemia. Hyperlipidemia significantly influence hepatic steatoses, but the mechanisms underlying PAR2 signaling are complex and have not yet been elucidated. To examine the modulatory action of FoxO1 and its altered interaction with PPARγ, we utilized db/db mice and PAR2-knockout (KO) mice administered with high-fat diet (HFD). Here, we demonstrated that PAR2 was overexpressed and regulated downstream gene expressions in db/db but not in db+ mice. The interaction between PAR2/β-arrestin and Akt was also greater in db/db mice. The Akt inhibition increased FoxO1 activity and subsequently PPARγ gene in the livers that led to hepatic lipid accumulation. Our data showed that FoxO1 was negatively controlled by Akt signaling and consequently, the activity of a major lipogenesis-associated transcription factors such as PPARγ increased, leading to hepatic lipid accumulation through the PAR2 pathway under hyperglycemic conditions in mice. Furthermore, the association between PPARγ and FoxO1 was increased in hepatic steatosis condition in db/db mice. However, HFD-fed PAR2-KO mice showed suppressed FoxO1-induced hepatic lipid accumulation compared with HFD-fed control groups. Collectively, our results provide evidence that the interaction of FoxO1 with PPARγ promotes hepatic steatosis in mice. This might be due to defects in PAR2/β-arrestin-mediated Akt signaling in diabetic and HFD-fed mice.